Da Imitatio Christi às normativas franciscanas : o processo de institucionalização da ordem dos frades menores (1209-1228) - Carmo, José Carlos Santos do (2019)
The present work aims to analyze the process of institutionalization of the Order of Friars Minor during the thirteenth century and understand the changes that occurred in the initial purpose of Francis of Assisi. For this analysis we start with the Gregorian Reformation, which began in the eleventh century and which, through the rise of canon law, established a own jurisdiction for the Roman Church, transforming it into the regulatory institution of Christendom and the religious groups that composed it This normalization directly affected the franciscans, initially organized in a fraternitas, but that due to the increase of the number of adepts and the narrowing of its relation with the papacy, soon would walk for an Ordo. These are important questions for us to understand the changes we see occurring in Francis' religious experience. It is in this sense that we analyze the documentation concerning the process of institutionalization of the Order, which began in 1209 and extended until 1228, in this way we use the Rules of 1221 and 1223, the Testament (1226), the Bulls Quo Elonganti, Ordinem Vestrum, Expositio super Regulam Fratrum Minorum and Expositio Quatuor Magistrotum Super Regulus Fratrum Minorum. It is clear in our study that, despite the changes imposed on the movement, the content of minority life based on an apostolic model has remained from one norm to another, however without the rigor that had been thought by the Poverello. It was necessary to reconcile the franciscanism from the beginnings with the institutional changes resulting from the transformation of the fraternitas in Ordo, this process occurred through interpretations around the franciscan documentation in the course of the thirteenth century.